Processing Chinese relative clauses in context by Italian L3 learners - Hu, Shenai; Toneatto, Carlo; Pozzi, Silvia; Guasti, Maria Teresa (Second language research, 2022)
The present study investigates third language (L3) learners’ processing of Chinese subject and object relative clauses in a supportive context. Using a self-paced reading task, we tested native Italian L3 learners of Mandarin Chinese and native Chinese speakers. The results showed that the L3 learners read significantly more slowly than the native speakers in all the target regions. Also, in the head noun region, they read object relative clauses significantly more slowly compared to subject relative clauses, indicating a preference for the latter. By contrast, for the native speakers, no significant differences were observed between subject and object relative clauses in any of the target regions. The L3 learners’ performance offers support for the Structural Distance Hypothesis over the Dependency Locality Theory, and the contrast between the two populations indicates that context is at play in the processing of relative clauses.